ANALISI PEREKONOMIAN DUA SEKTOR DALAM USAHA GETUK GORENG SOKARAJA BANYUMAS - Afsah Istiqomah; Nadea Indah Franesthi; Nadia Yulita Rahayu; Ulul Fadilah; Sarpini (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2024)
The purpose of this study is to examine how the two-sector economic model is applied in the Banyumas region, particularly in the Getuk Goreng Haji Tohirin enterprise. This paradigm emphasizes how households and businesses have a reciprocal interaction. Households serve as both final consumers and suppliers of labor and raw commodities. Conversely, manufacturers use domestic production elements to make products, such fried getuk, which are then sold to customers through distributors. This study demonstrates how the interdependent relationships between producers and consumers enable the two-sector economic model to promote local economic sustainability. It is anticipated that this study will add to the body of knowledge about the simple economy based on local knowledge.